2019
DOI: 10.1111/jfpp.14051
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drying kinetics and physicochemical properties of mulberry leather (pestil) dried with different methods

Abstract: The effects of microwave (90 and 180 W), hot air (60 and 70°C) and vacuum (60 and 70°C with 250 mbar) drying techniques on drying characteristics, total phenolic content (TPC), antioxidant capacity (AC), color and texture of mulberry pestils were investigated. L*, b*, C*, and h° decreased while a* value was generally increased in pestils. Hardness, springiness, chewiness, and gumminess of the samples were found to be significantly different (p < 0.05). Between the applied seven thin layer drying models, Page a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
2
12
0
2
Order By: Relevance
“…Similar results were also reported in literature. Suna and Özkan-Karabacak (2019) applied microwave drying to obtain mulberry leather at microwave powers of 90 and 180 W. They have stated that total phenolic compound increased with increasing microwave power. On the other hand, the extremely high microwave powers may cause decrement in total phenolic compounds due to a sudden increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were also reported in literature. Suna and Özkan-Karabacak (2019) applied microwave drying to obtain mulberry leather at microwave powers of 90 and 180 W. They have stated that total phenolic compound increased with increasing microwave power. On the other hand, the extremely high microwave powers may cause decrement in total phenolic compounds due to a sudden increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The application of drying air at 80°C in the first stage resulted in the higher firmness and adhesiveness values compared to single‐stage drying at 60°C and 15% RH, although the drying time was a little shorter. Suna and Özkan‐Karabacak (2019) studied mulberry leather drying and reported that the hardness (firmness) and adhesiveness of the dried mulberry leather product increased when dehydration occurred at a higher temperature. The drying condition in the second stage was expected to be more significant to the mango sheet texture than that of the first drying stage.…”
Section: Resultsmentioning
confidence: 99%
“…Plus, Stable Micro Systems Ltd., Godalming, UK) equipped with a light knife blade probe. The measurement method was modified from Suna and Özkan‐Karabacak (2019). The samples were cut into a rectangle shape and stacked one mango sheet upon another.…”
Section: Methodsmentioning
confidence: 99%
“…Phương pháp này thường được sử dụng chế biến trái cây sấy khô, đặc biệt phù hợp cho các doanh nghiệp chế biến quy mô vừa và nhỏ áp dụng. Trái cây sấy dạng miếng được chế biến chủ yếu từ trái cây có hoặc không bổ sung thêm các chất tạo cấu trúc, chất điều vị; do đó sản phẩm được xem là nguồn cung chất nhiều hợp chất có lợi cho sức khỏe như: các chất chống oxy hóa, vitamin C, chất khoáng, chất xơ [3,4]. Sản phẩm này có thể xem như là món ăn vặt có lợi cho sức khỏe thay thế cho các món ăn vặt giàu chất béo khác.…”
Section: đặT Vấn đềunclassified